Penerapan RFID dan WhatsApp Gateway untuk Monitoring Kehadiran Siswa secara Real-Time - Muh. Nurtanzis Sutoyo; Irna Irna; Sri Ayulestari; Anjun Anjun (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This study aims to design and implement a real-time student attendance system based on Radio Frequency Identification (RFID) integrated with a WhatsApp Gateway. The background of this research is the need for a fast and accurate attendance system that can instantly provide attendance information to parents. The research method adopts Research and Development (R&D) with a system development approach, including requirements analysis, system architecture design, development of a PHP and MySQL-based web application, integration of the WhatsApp Gateway API (e.g., Fonnte or Wablas), as well as functional and reliability testing. The black-box testing results show that all core functions, such as RFID reading, database recording, and notification delivery, operate as designed without errors. Meanwhile, the load test demonstrates that the system can process more than 500 transactions per minute with a notification delivery success rate of >=98% and an average latency of 2–3 seconds, meeting real-time service standards This system not only provides attendance reports accessible at any time but also enhances parental involvement through instant WhatsApp notifications. These findings confirm the reliability of RFID in automating attendance and introduce novelty through the integration of a WhatsApp Gateway, which has rarely been addressed in previous studies.Keywords: RFID; WhatsApp Gateway; Student Attendance; Real-Time; Attendance Monitoring AbstrakSistem absensi manual di sekolah masih lambat, rawan manipulasi, dan sulit direkap, sehingga diperlukan solusi presensi yang cepat dan akurat. Penelitian ini bertujuan mengembangkan sistem absensi siswa real-time berbasis RFID yang terintegrasi dengan WhatsApp Gateway untuk mengirimkan notifikasi otomatis kepada orang tua. Penelitian menggunakan pendekatan R&D melalui analisis kebutuhan, perancangan arsitektur, pengembangan aplikasi PHP MySQL, dan integrasi API WhatsApp. Pengujian dilakukan menggunakan metode black-box dan load test. Pada pengujian beban, sistem berhasil memproses hingga 800 transaksi dalam satu gelombang pemindaian puncak, yang merepresentasikan kondisi saat sebagian besar dari 830 siswa melakukan absensi dalam rentang waktu sangat singkat. Tingkat keberhasilan pengiriman notifikasi mencapai 98.7%, dengan latency rata-rata 2.7 detik. Seluruh fungsi berjalan sesuai rancangan tanpa kesalahan. Sistem ini terbukti cepat, stabil, dan efektif untuk mendukung monitoring kehadiran siswa secara real-time serta meningkatkan transparansi komunikasi antara sekolah dan orang tua.